Active Charcoal and Zeolite to Reduce COD and Ammonia of Domestic Wastewater - Rhenny Ratnawati; Sugito Sugito (Center for Journal Management and Publication, 2021)
Domestic wastewater contains high organic matter and nutrient. These compounds can be harmful for the environment if discharged directly to water bodies. Hybrid Anaerobic Baffled Reactor (HABR) technology might be a solution to overcome this problem. The present study aimed to investigate HABR technology for removal COD and ammonia in domestic wastewater. The HABR technology used 7 compartments with a suspended and an attachment system. Design of HABR reactor with is arranged in a series of laboratory scale with a size of 90 cm x 20 cm x 30 cm using activate charcoal (AC) and zeolite (ZE) media. The data collection process is carried out 5 days after seeding and acclimatization period. The collected data is presented in the form of table and figure containing data on the reduction of pollutant levels and efficiency. The highest COD removal value up to 63.77% and 57.22% occurred in AC dan ZE, respectively. The final COD concentration in AC dan ZE media was 67.75 mg/L and 80.00 mg/L. The highest ammonia concentration removal occurred in AC and ZE value up to 68.98%. and 73.47%, respectively. The final ammonia concentration in AC media and ZE was 9.37 mg/L and 8.01 mg/L. The final COD and ammonia concentrations in all treatments met the requirement of domestic wastewater quality standard according to Minister of Environment and Forestry Republic of Indonesia Decree No. 68 of 2016, where the COD and ammonia concentration should be 100.00 mg/L and 10.00 mg/L, respectively.